RADIATION DOSE REDUCTION IN BABYGRAM EXAMINATION ACCORDING TO DRLS (DIAGNOSTIC REFERENCE LEVELS) - Metria Riza Sativa; Lesi Yalestiati; Gatot Murti Wibowo (Wealth Community Empowerment, 2025)
Radiation dose reduction in pediatric radiography, particularly for babygram examinations, is a critical concern in modern healthcare. Infants and young children are highly sensitive to ionizing radiation, necessitating stringent protection measures to minimize potential long-term health risks. This study aimed to implement and evaluate Diagnostic Reference Levels (DRL)-based strategies for optimizing radiation doses in babygram procedures at RSUD Dr. Soedirman Kebumen. A socialization program was conducted for radiology staff, including radiologists, radiographers, and medical physicists, focusing on DRL application, ALARA principles, immobilization techniques, and collimation strategies. Results showed improved adherence to DRL guidelines, enhanced awareness among staff, and more effective use of dose reduction techniques. Evaluations indicated significant potential for dose reduction without compromising diagnostic quality. By incorporating advanced dose reduction techniques and conducting regular audits, this study concludes that implementing DRL-based strategies significantly enhances patient safety in pediatric radiography while maintaining diagnostic efficacy. Recommendations include prioritizing professional development, regular quality assessments, and expanding the use of DRLs alongside investments in automated planning technologies.Â